2021
DOI: 10.21203/rs.3.rs-368841/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child Maltreatment and associated Sociodemographic factors among Children affected by HIV/AIDS in Ghana: A Multi-Informant Perspective

Abstract: Background: Child maltreatment and its consequences are considered a major public health concern among children because they can cause significant physical and psychological problems. Child maltreatment is widespread but often underestimated. Surprisingly, there is hardly any data on the frequency of child maltreatment in general and particularly on orphans and vulnerable children in low-income countries. Method: This study employed cross-sectional, quantitative survey that involved 291 children aged 10–17 yea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Recent research has shown that in Ghana, households affected by HIV/AIDS frequently exhibit child abuse [21]. The substantial association between child abuse and psychological distress has also been demonstrated by other studies [20,22,23].…”
Section: Data and Samplementioning
confidence: 57%
See 1 more Smart Citation
“…Recent research has shown that in Ghana, households affected by HIV/AIDS frequently exhibit child abuse [21]. The substantial association between child abuse and psychological distress has also been demonstrated by other studies [20,22,23].…”
Section: Data and Samplementioning
confidence: 57%
“…The HIV/AIDS Impacted Families -Ghana Project, a wider research endeavour, provided the study's data [21]. In a communitybased cross-sectional study carried out in the Lower Manya Krobo Municipality in the Eastern Region of Ghana, information was collected from 291 youth between the ages of 10 and 17 years.…”
Section: Data and Samplementioning
confidence: 99%